IMPLEMENTASI KEBIJAKAN PENGELOLAAN PASAR BERIMAN KOTA TOMOHON - RUNTUWENE, BIRGITA; ROMPAS, WELSON; TULUSAN, FEMMY (JURNAL ADMINISTRASI PUBLIK, 2019)
This study aims to determine the implementation of the market management policies of the city of Tomohon and what are the constraints in the implementation. There are still many obstacles that are not in accordance with the implementation instructions. The involvement of all implementing parties has not guaranteed the success of a policy in Tomohon City Beriman Market. Utilization of market facilities that have not been in accordance with what they should. This research is to find out the implementation of Tomohon City Beriman Market management policy. The theory used as a reference or indicator uses the theory of Charles O Jones, namely, organizing, interpretation, and application / application. The method of this study uses a qualitative method with a descriptive approach. With his instrument as a researcher himself with eight informants.Data analysis techniques in the form of observation, interviews and documentation. The results showed that the implementation of the Tomohon City Beriman Market management policy had not run optimally in accordance with existing procedures. Even though it is seen from the existing conditions that coordination between the implementing parties, namely the Regional Market Company and the traders is already quite good and directed. Regional Market Companies have also carried out tasks in accordance with their functions and responsibilities as executors and managers with the SOP or Standard Operating Procedure, but not all of them are in accordance with the SOP or (Standard Operating Procedure), such as finding double stalls for one family lapak rental to third person, lack of awareness from market users who still see slum market conditions, MCK facilities that must be charged. The researcher gives advice on this research, which is to further optimize what has become the implementing procedure and as the implementing party the Regional Market Companies should be aware of their responsibilities as the manager.Keywords: Policy Implementation, Management of Public Market.